Structural insight and flexible features of NS5 proteins from all four serotypes of Dengue virus in solution. (1st November 2015) - Saw, Wuan Geok; Tria, Giancarlo; Grüber, Ardina; Subramanian Manimekalai, Malathy Sony; Zhao, Yongqian; Chandramohan, Arun; Srinivasan Anand, Ganesh; Matsui, Tsutomu; Weiss, Thomas M.; Vasudevan, Subhash G.; Grüber, Gerhard
Abstract : Infection by the four serotypes of Dengue virus (DENV‐1 to DENV‐4) causes an important arthropod‐borne viral disease in humans. The multifunctional DENV nonstructural protein 5 (NS5) is essential for capping and replication of the viral RNA and harbours a methyltransferase (MTase) domain and an RNA‐dependent RNA polymerase (RdRp) domain. In this study, insights into the overall structure and flexibility of the entire NS5 of all four Dengue virus serotypes in solution are presented for the first time. The solution models derived revealed an arrangement of the full‐length NS5 (NS5FL) proteins with the MTase domain positioned at the top of the RdRP domain. The DENV‐1 to DENV‐4 NS5 forms are elongated and flexible in solution, with DENV‐4 NS5 being more compact relative to NS5 from DENV‐1, DENV‐2 and DENV‐3. Solution studies of the individual MTase and RdRp domains show the compactness of the RdRp domain as well as the contribution of the MTase domain and the ten‐residue linker region to the flexibility of the entire NS5. Swapping the ten‐residue linker between DENV‐4 NS5FL and DENV‐3 NS5FL demonstrated its importance in MTase–RdRp communication and in concerted interaction with viral and host proteins, as probed by amide hydrogen/deuterium mass spectrometry. Conformational alterations owing to RNA binding are presented.